Queer in the digital lens: A qualitative study of experiences on geo-social networking apps - Srivastava, Akanksha; Arya, Yogesh Kumar; Joshi, Shobhna; Rai, Anurag (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Background: A significant portion of society invests a substantial amount of their time within the realms of the internet. Seeking meaningful and intimate connections, individuals frequently turn to geosocial apps as a conduit for potential relationships. This trend is particularly notable among those with non-binary or transgender identities, often contending with limited social support. Objective: The focal point of this study involves delving into the primary incentives driving individuals to engage with dating apps and concurrently examining the hurdles and difficulties they encounter during the usage. Method: Semi-structured interviews were taken from 7 transgender and non-binary individuals of age range 21 years to 27 years residing in India using the Grinder and Blued app. Thematic analysis was used for the generation of major themes of the study. Result: The major themes shedding light on motives for utilizing dating apps, encompass: 1) a journey of self-discovery regarding sexual identity, 2) the quest for romantic or intimate connections, 3) a pursuit of excitement and new experiences, 4) a sense of intrigue regarding others’ orientations and the hope to connect with like-minded individuals, and 5) a quest for validation of their gender identity, often inaccessible in offline settings. On the flip side, the salient recurring themes underscoring adverse experiences and hurdles faced by transgender individuals within dating apps include: 1) enduring verbal abuse and derogatory remarks, 2) encountering physical aggression, and 3) facing potential blackmail, especially for those navigating the complexities of disclosing their gender identity to their significant others. Conclusion: The findings of the present study illuminate a multitude of hurdles that transgender individuals confront while navigating dating apps. Furthermore, the study identifies the motivations driving their utilization of these applications, accompanied by several proposed recommendations to diminish the prevalence of harassment within this digital domain.